GAMBARAN KADAR HEMOGLOBIN IBU HAMIL BERDASARKAN KUALITAS TIDUR DI RUMAH SAKIT ANNISA PEKANBARU - Hotmauli Hotmauli; Brilian Dini Ma. Iballa; Harni Sepriyani (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2022)
Hemoglobin is a protein that binds oxygen, carbon dioxide and protons. The function of hemoglobin is to carry oxygen from the lungs throughout the body and to give red blood cells their color. Factors that trigger a decrease in hemoglobin levels are bleeding, genetic disorders, sleep disorders, unhealthy eating patterns and pregnancy. In a woman's pregnancy, a woman contains an embryo that starts from the embryo formed until the birth of the fetus. Physical changes of pregnant women such as body weight changes occur as well as changes in body posture. Pregnant women also experience fatigue, therefore sleep is very important for pregnant women. The purpose of this study was to describe the hemoglobin level of pregnant women at Annisa Hospital Pekanbaru based on sleep quality. This research uses cross sectional method. This study consisted of 33 respondents of pregnant women with 22 poor sleep quality and 11 good quality respondents. The hemoglobin levels of pregnant women were in the range of 9.0 – 11.7 g/dL. The conclusion of this study is that pregnant women with good sleep quality have an average hemoglobin level of 10.3 g/dl, while pregnant women with poor sleep quality have an average hemoglobin level of 9.4 g/dl.